MSA: A Multi-Key Block Encryption Algorithm with 3×3 Random Matrix Keys for Enhanced Data Security - Abdullah Abdulsamad; Mohanad Seyam; Samyrah Abu Irzayzah (AlQalam Journal of Medical and Applied Sciences, 2026)
This paper presents a novel block encryption and decryption algorithm, referred to as the MSA algorithm, which is fundamentally based on block-based cryptographic principles. In the proposed scheme, the plaintext is first arranged into a matrix of size and then partitioned into a set of matrix blocks. The MSA algorithm performs block encryption by encrypting each block independently using two distinct encryption keys that are automatically generated for each block. A unique pair of keys is assigned to every block, where the keys are square matrices with the same dimensions as the blocks and are generated through an indirect mathematical mechanism. Each element within a block is encrypted individually through a combined and highly complex mathematical process that simultaneously relies on both keys. This block-wise, element-level encryption significantly increases the algorithm’s complexity and enhances its resistance to cryptanalytic attacks. After encrypting all blocks, the ciphertext blocks are reassembled into an encrypted matrix that preserves the original dimensions of the plaintext matrix prior to block partitioning. During the decryption phase, the encrypted matrix is again divided into blocks. However, the decryption keys are mathematically generated from the original encryption keys and differ from them in both size and structure, as they are represented by matrices. These keys are produced through a controlled, randomized permutation of the encryption key elements. Each encrypted element is then decrypted individually using the corresponding decryption keys, ensuring accurate recovery of the original plaintext. The proposed MSA algorithm adopts an advanced block-based encryption methodology aimed at enhancing information security, providing effective protection for sensitive data, and reducing the risk of unauthorized access, thereby offering improved security and efficiency compared to many conventional block encryption schemes.